Behind the Scenes: A Review of Western Figure s’ Supportive Comments regarding the Qur’ān - Daneshgar, Majid (Al-Bayān, 2013)
Numerous supportive affirmations from non-Muslim scholars appeal to a great number of Muslims who endeavor to validate the Qur’ān’s sanctity as well as inimitability. This essay investigates the motives behind why various westerners or Europeans discuss the Qur’ān and Islam in such supportive manner, and how Muslims have interpreted those comments.